Pengaruh Kompetensi Pegawai, Pengalaman Kerja, dan Penempatan Kerja terhadap Kinerja Pegawai di DPMPTSP Kabupaten Pemalang - Sitohang, Cristian Atanasius; Kasmari Kasmari (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of employee competence, work experience, and job placement on employee performance at the Pemalang Regency Investment and One-Stop Integrated Service Office (DPMPTSP). The research method used was a descriptive quantitative approach, with data collection using a Likert-type questionnaire and data processing using multiple linear regression analysis. The results showed that employee competence had a positive but insignificant effect on employee performance, while work experience and job placement had a positive and significant effect. The conclusion of this study is that work experience and job placement are significant contributing factors to improving employee performance, while employee competence has not shown a statistically significant effect.   Keywords: Competence, Work Experience, Job Placement, Employee Performance, DPMPTSP